Shoulder arthrodesis in brachial plexus injuries--a review of six cases - Wong, E.L.; Kwan, M.K.; Loh, W.Y.C.; Ahmad, Tunku Sara (Malaysian Medical Association, 2005)
Shoulder arthrodesis is a secondary reconstructive option for patients with brachial plexus injuries requiring a stable shoulder. This study was undertaken to evaluate the clinical and radiological outcomes of shoulder fusion in six patients with flail upper limbs following complete brachial plexus injuries. The shoulder was fused in 30 degrees abduction, 30 degrees internal rotation and 30 degrees flexion via a direct lateral approach by using a 4.5 mm reconstruction plate without bone grafting. The average follow-up was 10.3 months. Radiological union was obtained in all patients. Five patients (83%) had relief of pain after the shoulder fusion. Improvement of function was observed in all patients with a mean improvement of 56.6 degrees (range 30 degrees-75 degrees) and 47.5 degrees (range 30 degrees-60 degrees) active flexion and abduction respectively. One patient developed humeral fracture distal to the plate and the fracture eventually healed with a splint. Successful stable fusion of the shoulder in patients with brachial plexus injuries requires rigid fixation with a single 4.5 mm reconstruction plate, protection of bone healing with a triangular abduction brace for 12 weeks and functional trapezius, levator scapulae, serratus anterior and rhomboid muscles for optimizing the functional result.